Pelatihan Creative Digital Content with Artificial Intelligence Bekerjasama dengan Dinas Perpustakaan dan Kearsipan Kota Mojokerto - Sanggarwati, Diah Ayu; Emmywati, Emmywati; Hayati, Cucu; Suprihandari, Miya Dewi (PUTRA JAWA PUBLISHER, 2024)
In recent years, artificial intelligence (AI) has become a very successful modern technology, often associated with human creativity. The Creative Digital Content with Artificial Intelligence training organized by STIE Mahardhika Surabaya and the Mojokerto City Library and Archives Service aims to raise the awareness and skills of participants in using AI to create innovative digital content. The method of implementation included lectures, discussions, and practical sessions. Despite facing some obstacles such as the constraints of computer devices and internet connections, the evaluations of the participants showed high satisfaction and great interest in this training. The results included improved knowledge and skills of participants in the use of AI for literacy and educational activities, as well as increased creativity and innovation in the creation of digital content.